Simplified Bernoulli's method significantly underestimates pulmonary transvalvular pressure drop. Issue 6 (19th November 2015) - Falahatpisheh, Ahmad; Rickers, Carsten; Gabbert, Dominik; Heng, Ee Ling; Stalder, Aurelien; Kramer, Hans‐Heiner; Kilner, Philip J.; Kheradvar, Arash
Abstract : Purpose: To determine whether neglecting the flow unsteadiness in simplified Bernoulli's equation significantly affects the pulmonary transvalvular pressure drop estimation. Materials and Methods: 3.0T magnetic resonance imaging (MRI) 4D velocity mapping was performed on four healthy volunteers, seven patients with repaired tetralogy of Fallot, and thirteen patients with transposition of the great arteries repaired by arterial switch. Pulmonary transvalvular pressure drop was estimated based on two methods: General Bernoulli's Equation (GBE), ie, the most complete form; and Simplified Bernoulli's Equation (SBE), known as 4 V 2 . More than 2300 individual pressure drop measurements were used to compare the simplified and the general Bernoulli's methods. A linear mixed‐effects model was employed for statistical analyses, fully accounting for clustering of observations among the methods and systolic phases. Results: The simplified Bernoulli's method systematically underestimated the pressure drop compared to general Bernoulli's method during the entire systolic phase ( P < 0.05), including the peak systole, where on average Δ p S B E / Δ p GBE = 78 % . Conclusion: The simplified Bernoulli method underestimated the pressure drop during all systolic phases in all the studied subjects. Therefore, it is necessary to take into account the flow unsteadiness for more accurate estimation of the pressure drop. J. Magn. Reson. Imaging 2016;43:1313–1319.